ENLISTED ORGANIZED LABOR IN OPPOSITION TO THE PROPOSED 'NO SMOKING' LEGISLATION (Tufts Archival Research Center, 2007)
List of organized labor in opposition to the proposed "no smoking" legislation. Identifies twenty-six leaders of various unions, primarily in New York.